iPhone 4 Made Simple - Trautschold, Martin (Apress, 2012)
In your hands is one of the most exciting devices to hit the market in quite some time: the iPhone 4. This Quick Start Guide will help get you and your new iPhone 4 up and running in a hurry. You’ll learn all about the buttons, switches, and ports, and how to use the innovative and responsive touch screen and multitask with the new App Switcher bar. Our App Reference Tables introduce you to the apps on your iPhone 4—and serves as a quick way to find out how to accomplish a task.